2013
DOI: 10.1080/03055698.2013.814561
|View full text |Cite
|
Sign up to set email alerts
|

Role of peers in student academic achievement in exogenously formed university groups

Abstract: We estimate the influence of classmates' ability characteristics on student achievement in exogenously formed university student groups. The study uses administrative data on undergraduate students at a large selective university in Russia. The presence of high-ability classmates has a significant positive effect on individual grades in key economics and mathematics courses as well as on overall academic performance. While a simple linear-in-means model reveals moderate peer effects, non-linear specifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Social influence is an important mechanism in social capital building in small groups, but the relationship between social capital and study success during the first year may depend on the high school achievement level of incoming students. Androushchak, Poldin, and Yudkevich (2013) find a nonlinear effect of peer support on achievement. High-ability students obtained the most benefit from interacting with other high-ability fellow students, whereas low-ability students were not influenced by fellow students, nor did they affect other fellow students.…”
Section: Prior Achievement and Self-efficacymentioning
confidence: 87%
“…Social influence is an important mechanism in social capital building in small groups, but the relationship between social capital and study success during the first year may depend on the high school achievement level of incoming students. Androushchak, Poldin, and Yudkevich (2013) find a nonlinear effect of peer support on achievement. High-ability students obtained the most benefit from interacting with other high-ability fellow students, whereas low-ability students were not influenced by fellow students, nor did they affect other fellow students.…”
Section: Prior Achievement and Self-efficacymentioning
confidence: 87%
“…During the interviews, nearly all students said that peers had been essential in negotiating discourse, understanding expectations, and improving their work. Findings highlighting the key role of peers in developing the necessary competencies, knowledge and attitudes to engage in a variety of discursive episodes seem consistent with the literature that stresses the importance of dialogue and interactions with peers in learning contexts (Androushchak et al, 2013;Bruner, 1978;Carrell et al, 2009;De Paola & Scoppa, 2010;Epple & Romano, 2010;Moore et al, 2016;Orsmond et al, 2101;Seloni, 2012;Swain, 2001;Vygostky, 1978;Wood et al, 1976;Zappa-Hollman, 2007).…”
supporting
confidence: 80%
“…In a recent literature review, Epple & Romano (2010) concluded that the evidence in different studies left little doubt as to the effect of peers both within and outside the classroom. Furthermore, there is increasing evidence of positive peer effects in student achievement in higher education (Androushchak et al, 2013;Carrell et al, 2009;De Paola & Scoppa, 2010;Moore et al, 2016).…”
mentioning
confidence: 99%
“…The benefit of collaborating and group learning has been documented by many researchers. They support the ideas that peer interaction and peer collaboration within small groups can facilitate better understanding (Ames & Murray, 1982;Androushchak, Poldin, & Yudkevich, 2013;Berndt, 1987;O' Donnell & King, 1999;Oktay, 2017), motivation and confidence (Burdett & Hastie, 2009;Hammond, Bithell, Jones, & Bidgood, 2010). A literature review research conducted by Reise, Samara and Lillejord (2012) have found that peer learning (1) positive effects on students' achievement, (2) reduces the teachers' workload, and (3) develops generic basic skills.…”
Section: Introductionmentioning
confidence: 67%